Engineering students' perceptions towards the use of a vocabulary mobile application in learning technical vocabulary - Mohd Amir Izuddin, Mohamad Ghazali (2017)
The current study aims at examining the engineering students' perception towards the use of mobile application, namely VocBlast in assisting them to learn technical vocabulary as well as to analyze the perceived usefulness of using VocBlast among genders. The study only focuses on two key elements which are the perceived impact of using VocBlast to learn technical vocabulary and the features in VocBlast that assist engineering students to learn technical vocabulary. The data was collected by employing a mixed method in which qualitative method was used as the main source of data collection. Data gained from the qualitative data was used to formulate questionnaire for the purpose of collecting quantitative data. Results from the study illustrate that the students perceived VocBlast to have increased their technical vocabulary knowledge especially in spelling and definition. Findings from the research show that there are several features that students like about VocBlast. The quantitative result suggests that there is no significant difference between genders in the impact of using VocBlast to learn technical vocabulary. Also, no significant difference was found among genders in term of the feature in VocBlast that assists them to learn technical vocabulary. In conclusion, this study has proven that vocabulary mobile application can offer valuable contributions to the technical vocabulary learning experience among the engineering students.